An effective method for establishing a regeneration and genetic transformation system for Actinidia arguta - Wantian Yao; Lingling Kong; Diya Lei; Bing Zhao; Honglan Tang; Xuan Zhou; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Mengyao Li; Qing Chen; et al. (Frontiers in Plant Science, 2023)
The all-red A. arguta (Actinidia arguta) is an anthocyanin-rich and excellent hardy fruit. Many studies have focused on the green-fleshed A. arguta, and fewer studies have been conducted on the all-red A. arguta. Here we reported a regeneration and Agrobacterium-mediated transformation protocol by using leaves of all-red A. arguta as explants. Aseptic seedling leaves of A. arguta were used as callus-inducing materials. MS medium supplemented with 0.3 mg·L-1 2,4-D and 1.0 mg·L-1 BA was the optimal medium for callus induction of leaves, and medium supplemented with 3 mg·L-1 tZ and 0.5 mg·L-1 IAA was optimal for adventitious shoot regeneration. The best proliferation medium for adventitious buds was MS + 1.0 mg·L-1 BA + 0.3 mg·L-1 NAA. The best rooting medium was 1/2MS + 0.7 mg·L-1 IBA with a 100% rooting rate. For the red flesh hardy kiwi variety ‘Purpurna Saduwa’ (A. arguta var. purpurea), leaves are receptors for Agrobacterium (EHA105)-mediated transformation. The orthogonal experiment was used for the optimization of each genetic transformation parameter and the genetic transformation of the leaves was 21% under optimal conditions. Our study provides technical parameters for applying genetic resources and molecular breeding of kiwifruit with red flesh.